The Transmission Properties of Coated THz Teflon Tube - Wu Pan; Tian bo Duo; Zichen Liu; Jun Chen (Institute of Advanced Engineering and Science, 2014)
The S parameters, attenuation characteristics and group delay characteristics of the Teflon tube have analyzed in the paper. Firstly, the S parameters of metal and polymer tube with the same structure are compared. Then the transmission properties of the simple terahertz Teflon tubes and terahertz Teflon tubes which are coated metal film by three different ways are simulated, and the advantages and disadvantages are contrasted. The S parameters of Teflon tube are more ideal, but it is not plain, the attenuation within the working frequency is less than 10.77dB/m, the group delay is less than 10-10s, coating Teflon tube with film can make S parameters plain. Teflon tube can transmit THz wave effectively, and if the Teflon tube is coated with films, the transmission characteristics can be improved in conclusion.